Relasi Negara Dan Agama Dalam Konteks Politik Islam: Kajian Komparatif Antara Ibnu Taimiyyah Dan Muhammad Abduh - Ayuningtiyas, Santi (Tim Jurnal STAI KH. Zainuddin Ponpes Mojosari, 2024)
The relationship between state and religion in Islamic politics has become a crucial issue, especially through the perspectives of two prominent thinkers, Ibn Taymiyyah and Muhammad Abduh. This study aims to understand how these two figures view the relationship between sharia and governance and the contribution of their ideas to contemporary Islamic political discourse. Library research is employed as the research method, encompassing a literature review from books, journal articles, and other secondary sources to achieve a comprehensive analysis of their thoughts. The findings reveal that Ibn Taymiyyah supports implementing sharia as the foundation of the state, emphasizing the importance of religious tradition and authority in political governance. Conversely, Muhammad Abduh offers a more rational, adaptive approach, emphasizing the need for education and Islamic thought reform to meet modern demands. Although they come from different viewpoints, both provide significant contributions tointegrating Islamic values within political practice. This study concludes that both Ibn Taymiyyah and Muhammad Abduh remain relevant in facing today’s socio-political challenges, illustrating the need for a dynamic dialogue between tradition and modernity within Islam.